Hemoglobin genotype variants and Plasmodium Falciparum malaria in children receiving postpartum care at Faith Alive Foundation Jos, Plateau State, Nigeria - Njila HL; Idoko JE; Ombugadu A; Zakari H (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
More and more data are showing a link between hemoglobin genotypes and Plasmodium falciparum malaria. In order to establish the prevalence of hemoglobin genotype variants and their association with P. falciparum malaria in children receiving postpartum care at Faith Alive Foundation Jos, Plateau State, we study the distribution of these variants. From each sample, thick and thin blood films were created, and hemoglobin genotypes were determined using electrophoresis. Out of 172 samples examined, 131 (76.16%) were infected with P. falciparum malaria while 41 (23.84%) were not infected. There was no significant difference (p > 0.05) in the distribution of P. falciparum malaria in relation to hemoglobin genotypes. P. falciparum malaria was highest in AA with 92 (70%) and SS was the least with 12 (9%). There was no significant difference (p > 0.05) in th+++e prevalence of P. falciparum malaria in relation to age. P. falciparum malaria infection was highest in the age group ≥ 12 months than age group 0 - 11 months. There was no significant difference (p > 0.05) in the prevalence of P. falciparum malaria in relation to sex. The result depicted that P. falciparum malaria infects more males than females. There was also no significant difference (p > 0.05) in the prevalence of P. falciparum malaria in relation to months. The month of September had the highest prevalence of P. falciparum malaria followed by October and August respectively. It is, therefore, recommended that public health education campaigns for mothers and healthcare givers be intensified to create awareness that will lead to the reduction of human-vector contact, especially in children.